PENTINGNYA LITERASI MEDIA BAGI KAUM PEREMPUAN - Rahmi Mulyasih (LONTAR: Jurnal Ilmu Komunikasi, 2016)
This study focuses on the importance of media literacy for women, this is because women are the main characters in a family, the young generation of quality born of the important role of women. This study used a qualitative approach with phenomenological research methods. The results showed that the low culture of literacy in women, which can ultimately result in terbiasanya children watch the action Kekeran and low values of humanist obtained children from an early age, resulting in the shift of the culture and behavior of the young generation that is far from the value of -the value of religion and society.